Dialogic Communication and Public Trust in Health Emergencies - Hidayat, Rachmat; Nurhasanah; Pratama, Muhammad Anzarach (Yayasan Sinergi Kawula Muda, 2025)
This narrative review examines the role of strategic communication in crisis management, focusing particularly on its effectiveness in fostering public trust during the COVID-19 pandemic. The study aims to explore how transparent, responsive, and technology-integrated communication strategies influence collective behavior and institutional legitimacy. Using literature sourced from databases such as Scopus, Web of Science, and PubMed, this review applies thematic analysis to synthesize findings across three dimensions: government public communication, digital media engagement, and internal organizational resilience. The results reveal that governments employing multimodal communication—combining factual messaging, symbolic narratives, and interactive channels—are more successful in promoting compliance and minimizing misinformation. Countries with open, participatory approaches generally report higher levels of public trust compared to those with top-down, controlled messaging. Additionally, media digitalization facilitates real-time feedback, enhances public engagement, and contributes to crisis transparency. However, systemic challenges such as fragmented communication systems, lack of adaptive training, and weak interagency coordination remain prevalent. These findings suggest the need for integrated policy frameworks that emphasize proactive, dialogic, and technologically enhanced communication strategies. Future studies should focus on developing context-specific models that accommodate cultural and institutional nuances. This review underscores that strategic communication is an indispensable pillar of effective crisis management and should be embedded as a fundamental element of public governance systems.